Agritourism and Kidding Season: A Large Outbreak of Human Shiga Toxin-Producing Escherichia coli O157 (STEC O157) Infections Linked to a Goat Dairy Farm—Connecticut, 2016 - Nichols, Megin C.; Gacek, Paul; Phan, Quyen; Gambino-Shirley, Kelly J.; Gollarza, Lauren M.; Schroeder, Morgan N.; Mercante, Alexandra; Mullins, Jocelyn; Blackstock, Anna; Laughlin, Mark E.; Olson, Samantha M.; Pizzo, Eugene; et al. (Frontiers in Veterinary Science, 2021)
The objective of this study was to determine sources of Shiga toxin-producing Escherichia coli O157 (STEC O157) infection among visitors to Farm X and develop public health recommendations. A case-control study was conducted. Case-patients were defined as the first ill child (aged<18 years) in the household with laboratory-confirmed STEC O157, or physician-diagnosed hemolytic uremic syndrome with laboratory confirmation by serology, who visited Farm X in the 10 days prior to illness. Controls were selected from Farm X visitors aged<18 years, without symptoms during the same time period as case-patients. Environment and animal fecal samples collected from Farm X were cultured; isolates from Farm X were compared with patient isolates using whole genome sequencing (WGS). Case-patients were more likely than controls to have sat on hay bales at the doe barn (odds ratio: 4.55; 95% confidence interval: 1.41–16.13). No handwashing stations were available; limited hand sanitizer was provided. Overall, 36% (28 of 78) of animal and environmental samples collected were positive for STEC; of these, 64% (18 of 28) yielded STEC O157 highly related by WGS to patient isolates. STEC O157 environmental contamination and fecal shedding by goats at Farm X was extensive. Farms should provide handwashing stations with soap, running water, and disposable towels. Access to animal areas, including animal pens and enclosures, should be limited for young children who are at risk for severe outcomes from STEC O157 infection. National recommendations should be adopted to reduce disease transmission.